Three new species of Cerviniella Smirnov, 1946 (Copepoda: Harpacticoida) from the Arctic - Kihara, Terue C.; Arbizu, Pedro Martínez (Zootaxa, 2012)
Considered one of the most common harpacticoid families in deep-sea benthos, the Aegisthidae can be found in varioustypes of marine sediments and at different depths. During the fourth leg of the ninth expedition of RV Polarstern in theArctic Ocean (ARK-IX/4) in September 1993, three new representatives of the genus Cerviniella were collected in mul-ticorer samples from the Laptev Sea at depths of 760-2017 m. The new species have a close relationship, as indicated by thecombination of shared characters: distal segment of antennule with aesthetasc, antennary endopod with two setae and one spinelaterally, and four spines and three setae apically; and the same number of armature elements on the maxillula and maxilla.Cerviniella danae sp. nov. and C. hitoshii sp. nov. can be easily distinguished from their congeners primarily by the reductionof the antennules to only five segments, which is common to both species but unique in Cerviniella. Cerviniella danae sp. nov.is most readily separated from other described species by the armature of the antennule and maxilliped, and the spine and setaformulae of the swimming legs. For C. hitoshii sp. nov., major diagnostic differences are found in the maxilliped, segmentationand setation of P3 and P4 endopods, and P6 represented by three setae. Cerviniella arctica sp. nov. is unique in the combinationof the following characters: caudal rami extremely elongated, armature of the antennules and mandible, and the spine and setaformulae of the swimming legs. Based on a review of the literature, an updated listing of the P1-P4 armature and a key to species of the genus are presented.